DEVELOPMENT OF CERVICAL INTRAEPITHELIAL NEOPLASIA AND INVASIVE CERVICAL CANCER DUE TO OXIDATIVE STRESS - Asotic Amir; Asotic Memic Anida; Memic Muhamed; Asotic Kerim; Asotic Amra (Sanamed, 2024)
Background: Cervical cancer (CC) ranks third among all malignant diseases of the female reproductive system. CC arises through a series of pathological changes called cervical intraepithelial neoplasia (CIN). Timely diagnosis and treatment of CIN are essential in the prevention of CC. Oxidative stress (OS) presents a major risk factor in the pathogenesis of both CC and CIN. This study aimed to determine the association between OS and the pathohistological severity of cervical lesions.